Empowering Junior High School Cultural Arts Teachers Through Wreigrapy Training in Tanah Datar Regency - Ariusmedi, Ariusmedi; Zubaidah, Zubaidah; Syafei, Syafei; B, Ega Harna (International Journal of Educational Dynamics, 2024)
The goal of this program is to enhance the skills of Junior High School Cultural Arts teachers in Tanah Datar Regency through training in Fine Arts, specifically Wreigrapy (Screen Printing). The program consisted of three phases: planning, implementation, and evaluation. Methods included lectures, demonstrations, and Q&A sessions, focusing on equipping teachers with practical skills and creative techniques. Results showed significant improvements in participants’ understanding of Fine Arts, with 90% successfully producing serigraphy artworks that could be applied as teaching materials. The program addressed a critical gap in Fine Arts education, providing teachers with innovative tools to enrich the curriculum and foster creativity among students. Although the outcomes were largely positive, further training is needed to achieve excellence in skill application. This initiative highlights the potential of Fine Arts to inspire entrepreneurial skills and broaden students' artistic horizons.